2016
DOI: 10.1155/2016/1685362
|View full text |Cite
|
Sign up to set email alerts
|

Piloting Psychology Annual Reviews as a Method of Measuring Psychological Distress and Quality of Life in Paediatric Renal Transplant Patients

Abstract: Psychosocial distress and poorer quality of life after renal transplantation are common in children and young people. This has implications for medication adherence and survival. Posttransplant psychology annual reviews were introduced in one Paediatric Renal Service in the UK as a means of measuring psychological distress and quality of life, as well as facilitating identification of patients and parents/carers who would benefit from psychological intervention. The process of completing posttransplant psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The results of this systematic review show that PROMs are being used in the field of pediatric solid organ transplant . However, researchers advise that both generic and disease‐specific instruments are used to conduct a comprehensive evaluation of health status and overall QOL to generate more accurate depictions of a patient's health‐related QOL .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this systematic review show that PROMs are being used in the field of pediatric solid organ transplant . However, researchers advise that both generic and disease‐specific instruments are used to conduct a comprehensive evaluation of health status and overall QOL to generate more accurate depictions of a patient's health‐related QOL .…”
Section: Discussionmentioning
confidence: 99%
“…The perception of QOL of children regardless of the treatment modality for ESKD was better compared to the evaluation of parents, especially in the areas of general fatigue, family and peer interaction and concern (7,8,(11)(12)(13)(14)16) . PedsQL data revealed that the concern parents present related to the social function of their children was not observed on the children themselves (8) .…”
Section: Discussionmentioning
confidence: 87%
“…The choice of instrument for assessing QOL during childhood must meet the criteria of reliability and understanding from the public. The instruments analyzed in this study are not available for use in Brazil and require translation and adaptation for the Portuguese language (8) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations